ANALISIS PERILAKU PEMILIH DALAM PEMILU PRESIDEN AMERIKA SERIKAT DI ARIZONA TAHUN 2020 (Jurnal Nawala Politika, 2023)
This study aims to determine voting behavior in the state of Arizona in the 2020 United States presidential election. In the election process, what factors affect voter behavior in Arizona, basically there are many factors that can influence people's choices. This study uses the literature review method obtained from secondary data analysis. There are several findings as follows: Voter behavior in the state of Arizona in the 2020 United States presidential election is influenced by several factors including sociological factors, psychological factors and rationality factors. These three factors are the most influential in voter behavior. Keywords: Election, Arizona, Voter Behavior.